Preliminary analysis of the efficiency of non-standard divertor configurations in DEMO. (August 2017) - Subba, F.; Aho-Mantila, L.; Ambrosino, R.; Coster, D.P.; Pericoli-Ridolfini, V.; Uccello, A.; Zanino, R.
Highlights: Analyzed DEMO expected operational space. Compared Standard Divertor, X-Divertor and Super X-Divertor. X-Divertor shows better performances than Super X-Divertor. Abstract: The standard Single Null (SN) divertor is currently expected to be installed in DEMO. However, a number of alternative configurations are being evaluated in parallel as backup solutions, in case the standard divertor does not extrapolate successfully from ITER to a fusion power plant. We used the SOLPS code to produce a preliminary analysis of two such configurations, the X-Divertor (XD) and the Super X-Divertor (SX), and compare them to the SN solution. Considering the nominal power flowing into the SOL ( PSOL = 150 MW), we estimated the amplitude of the acceptable DEMO operational space. The acceptability criterion was chosen as plasma temperature at the target lower than 5 eV, providing low sputtering and at least partial detachment, while the operational space was defined in terms of the electron density at the outboard mid-plane separatrix and of the seeded impurity (Ar only in the present study) concentration. It was found that both the XD and the SXD extend the DEMO operational space, although the advantages detected so far are not dramatic. The most promising configuration seems to be the XD, which can produce acceptable target temperatures at moderate outboard mid-plane electron density ( n o m p = 4.5 × 10 19 m −3 ) and Zeff = 1.3.